Budaya Patriarki masyarakat Migran Bali Di Desa Kertoraharja Kecamatan Tomoni Timur Kabupaten Luwu Timur - Ulfa Utami Mappe; Jusnawati Jusnawati (SOSIORELIGIUS, 2022)
Abstract The patriarchal culture of the Balinese migrant community results in discrimination against women in various aspects. This study aims to determine the application of the patriarchal system to Balinese migrant communities in Kertoraharjo village and why this patriarchal system is still maintained. This research is a qualitative research, using data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the application of this patriarchal system is embodied in Balinese customary or cultural rules that have been believed by previous generations. First, the difference in the value of children based on gender, boys are more important than girls. Second, division of tasks and roles covering three important domains; domestic, public, and religious rituals. Women do heavier work than men. Third, the division of inheritance. Women are not entitled to the inheritance of their parents or the assets acquired by their husbands after marriage, while men have full rights. This subordination to women is still maintained because of the strong influence of Balinese culture brought by migrant communities, the lack of education that women receive, the upbringing pattern that is passed down from generation to generation from the family environment. Keywords: Patriarchal System, Balinese Society, Migrants